Konsep Profit and Loss Sharing (PLS) Berbasis Surah Al-Mulk - Namira Amalia Assagaf (JIATAX (Journal of Islamic Accounting and Tax), 2019)
This study aims to restore human consciousness related to the concept of Profit and Loss Sharing (PLS) on the order of justice and welfare distribution based on Surah Al-Mulk. This research is a qualitative research with a descriptive-qualitative approach. The data collected in this study are secondary data obtained from literature studies of the literature related to problems in the study. The data obtained were then analyzed using descriptive analysis methods. The result of this research is that Al-Mulk surah is able to make people aware of always presenting Allah in all their activities, so that they can avoid the actions that He forbids. Therefore, this researcher uses surah al-Mulk as the basis for the application of the PLS concept.